PRELIMINARY ASSESSMENT OF METAL BIOAVAILABILITY TO PLANTS IN THE NEVES CORVO AREA OF PORTUGAL - FARAGO, M. E.; COLE, M.; XIAO, X. Y.; VAZ, M. C. (CHEMICAL SPECIATION AND BIOAVAILABILITY, 1992)
Cistus species and Quercus rotundifolia were collected from near the Neves Corvo copper mine and from an area 12 km from the mine. These species are widely distributed in southern Portugal. Aerial parts of the plants have been analysed and the concentrations of elements in the plants have been compared with those of the soils. There is more copper available in the soils near the mine, and this is reflected in an accumulation of copper in both Cistus and Quercus tops. Both plants can be considered to be of the following general types: accumulators of Cu in the mine area; excluders of Mo and Ni; concentration indicators of Pb and possibly Zn. We conclude that both copper and lead have migrated from the concealed orebody through geological faults. These elements in the soil resulting from the ore deposit contribute large portions ot the available metals near the mine area. It is further concluded that there is aerial contamination near to the mining activities, but copper from this source is less available to the plants.
The following values have no corresponding Zotero field: pub-location: PO BOX 314, ST ALBANS AL1 4ZG, HERTS, ENGLAND publisher: SCIENCE REVIEWS 2000 LTD
Keywords: CISTUS SPECIES; MINES; OREBODY; QUERCUS-ROTUNDIFOLIO